If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (2X) + (2X + 5) = 100 Reorder the terms: X + (2X) + (5 + 2X) = 100 Remove parenthesis around (5 + 2X) X + (2X) + 5 + 2X = 100 Reorder the terms: 5 + X + (2X) + 2X = 100 Combine like terms: X + (2X) = 3X 5 + 3X + 2X = 100 Combine like terms: 3X + 2X = 5X 5 + 5X = 100 Solving 5 + 5X = 100 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 5X = 100 + -5 Combine like terms: 5 + -5 = 0 0 + 5X = 100 + -5 5X = 100 + -5 Combine like terms: 100 + -5 = 95 5X = 95 Divide each side by '5'. X = 19 Simplifying X = 19
| 7+3p-5=8p+6-3p | | 1/3y-3=5 | | 2y-8=-x | | -1=(v-2)/21 | | 14=.01875x^2+.1575x+1.5 | | (2n^2+1)= | | 5x+2-7x=6+2x | | -3x-149=85+10x | | x+(X*2)+(X*2+5)=100 | | 9x+3=27x | | 4=4x+3 | | (-2z^3/x)^3 | | 95-10x=45 | | (-9+a)/15=1 | | -102-2x=60+4x | | 12=-2/7v | | 7/8-1/6 | | 6y=3x+12 | | f(0)=0-0+1 | | 3x+3-6x=8+2x | | 10x-16x=48 | | -3x-4=29 | | -15-x=12-2x | | f(-1)=1-1+1 | | f(9)=81-9+1 | | -56-7x=-10x+16 | | 5x+150=8x+264 | | 7x+2=24 | | 11x+4=7x+3 | | f(1)=1-1+1 | | -16+3(x-5)=2(x+4) | | 8x+124=180 |